Copper-Catalyzed Synthesis of Alkyl-Substituted Pyrrolo[1,2-a]quinoxalines from 2-(1H-Pyrrol-1-yl)anilines and Alkylboronic Acids - Guan, Xin; Yan, Rulong (Synlett, 2020)
A radical pathway for the construction of pyrrolo[1,2-a]quinoxalines by using 2-(1H-pyrrol-1-yl)anilines and alkylboronic acids has been developed. Features of this process include Cu catalysis, readily accessible starting materials, and simple operations. Alkylboronic acids are used for the construction of pyrrolo[1,2-a]quinoxaline derivatives, and the desired products are obtained in moderate yields.
Keywords: pyrrolylanilines; alkylboronic acids; pyrroloquinoxalines; radical reaction